Production level of tetrodotoxin in Aeromonas is associated with the copy number of a plasmid. (July 2015) - Liu, Jing; Wei, Fen; Lu, Ying; Ma, Tinglong; Zhao, Jing; Gong, Xiaoling; Bao, Baolong
Abstract: Tetrodotoxin (TTX) has been identified from taxonomically diverse organisms. Artificial synthesis of TTX has been reported, but the biosynthetic pathway of TTX remains elusive. In this study, we found TTX producing ability was associated with the copy number of plasmid pNe-1 in Aeromonas strain Ne-1 during fermentation, suggesting that at least one gene encoding a TTX-synthesis enzyme is located on this plasmid. Compared with bacterial genomes, plasmids are small and easier to screen for genes associated with TTX biosynthesis. The approximately 100 kb genome of pNe-1 was sequenced. The plasmid contains 60 complete open reading frames (orfs) of which 32 (53.3%) encode hypothetical proteins. Seven genes are related to the type IV secretion system (T4SS) and 2 genes are related to transposons, indicating that the TTX-producing bacterium Aeromonas might have the ability to transfer the TTX biosynthesis gene via the conjugation and contagion of plasmid pNe-1. In addition, we unexpectedly found that Aeromonas Ne-1 contains unknown TTX-degrading materials, indicating there is a homeostatic mechanism to maintain a stable amount of TTX in the bacterium. These results will help us to better understand TTX biosynthesis, the bacterial origin of TTX, and TTX degradation. Highlights: TTX producing ability of Aeromonas was associated with the copy number of plasmid. The plasmid in bacterium Aeromonas contains the genes of mobile genetic elements. A TTX-producing bacterium Aeromonas also has TTX-degrading ability.